Linking financial development and economic growth: do we have new evidence of the role of institutions in CFA countries? - Christelle Meniago; Brian Tavonga Mazorodze; Gisele Mah (Cogent Economics & Finance)
This paper examines the relationship between financial development and economic growth in Communauté Financière Africaine (CFA) countries from the period 2003 to 2018. Drawing from a diverse dataset covering 13 countries, this research utilizes the Fully Modified Ordinary Least Squares technique to analyze the data. The findings reveal a significant positive relationship between financial development and economic growth, underscoring the importance of effective financial systems in fostering economic growth. Furthermore, the results emphasize the pivotal role of institutional quality on this relationship further demonstrating that while financial development acts as a catalyst for growth, its impact also relies on the quality of institutions. On the policy and practical front, the study suggests that policymakers in CFA countries should focus on expanding financial services and improving financial infrastructure. This could include making banking and credit more accessible for individuals and businesses, developing better financial markets, and making financial services more efficient. Additionally, the study recommends that improvements in the financial sector should go together with broader reforms in institutions. This means implementing policies that not only boost financial development but also strengthen institutional quality, thereby creating a strong and supportive environment for economic growth.